Pengembangan Video Pembelajaran Berbasis Problem Based Learning Pada Pembelajaran Muatan IPS Kelas V SDN 1 Panji Tahun Pelajaran 2022/2023 - Pinem, Nima Klarisa; I Nyoman Jampel (Journal for Lesson and Learning Studies, 2023)
The lack of learning media appropriate to student needs will affect student learning outcomes. This study aims to produce instructional video learning media products that are tested for validity. This type of research is developed with the ADDIE model. The subjects involved in this research were content experts, design experts, media experts, and 37 fifth-grade elementary school students. Data collection in the study was carried out using test and non-test methods, with research instruments in the form of learning achievement tests and media product validity questionnaires. The data obtained in the study were then analyzed using qualitative and quantitative analysis techniques. The research analysis showed that problem-based learning video media products were declared valid with the results of subject matter expert reviews of 92.30% (very good). Learning design experts at 90.00% (very good). Learning media experts 96.15% (very good). Student questionnaire responses, namely individual trials, 94.33% (very good), and small groups, 92.11% (very good). Problem-based learning video media products are effectively used. Based on these results, problem-based learning video media can improve student learning outcomes.